Effectiveness of Compost and NPK Application on Tomato Plant Growth and Yield (Solanum Lycoprisicum L) - M Azizi (SEAS (Sustainable Environment Agricultural Science), 2026)
Abstract Tomatoes are a versatile crop that can be consumed fresh or used in the pharmaceutical, cosmetic, and food processing industries. Their vitamin and mineral content is beneficial to health. Organic fertilizers, derived from the decomposition of natural materials such as plant residues and animal manure, can improve soil fertility—particularly in slightly acidic soils—by enhancing soil structure and microbial activity. Tomato plants require large amounts of the nutrients N, P, and K. This study was conducted at the Faculty of Agriculture, University of Papua, Manokwari, from January to March 2026. Research Design: The research was designed using a randomized block design (RBD) with a factorial pattern consisting of two factors. The factors in this study are: The factors in this study are: the compost dose treatment factor (C), which consists of 3 levels, namely: C0: Control, C1: 0.2 ml/L, C2: 0.4 ml/L, The NPK (N) dosage factor consists of 3 levels, namely: N0: Control C1: 0.2 ml/L, C2: 0.4 ml/L, The NPK (N) dosage factor consists of 3 levels, namely: N0: Control, N1: 0.2 ml/L, N2: 0.4 ml/L. This study employed a factorial randomized block design (RBD) comprising 9 treatment combinations, each with 3 replicates, resulting in a total of 27 experimental units. Data were analyzed using Analysis of Variance (ANOVA) and yielded significantly different results, followed by a 5% BNJ analysis. The observed variables included plant height (cm), number of leaves, stem diameter (cm), number of fruits, and fruit weight. Based on these results, it can be concluded that the application of compost hormones had no effect on any of the observed variables. The application of gibberellin hormones had a significant effect on fruit diameter, number of fruits, and fruit weight per plant but had no significant effect on plant height and number of leaves